Construção de eletrodo de pasta de carbono modificado com bagaço de cevada (Hordeum vulgare) e aplicação na determinação de íons chumbo (II) em amostras de batom - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Chemical analysis increasingly requires techniques with high sensitivity, practicality and low cost. In this sense, redissolution voltammetry is a technique that, in relation to the cost-benefit in metal analysis, is efficient and inexpensive in relation to other techniques involving high equipment cost, use of high value gases, and limitation of analysis in situ Voltammetric techniques are even more effective using modified electrodes for specific analyzes. Natural adsorbents are examples of electrode modifiers and the literature provides good information in this regard. Barley bagasse (Hordeum vulgare) (BC) is a residue of the brewing industry, the literature presents satisfactory results of the use of this material in the adsorption of metals, such as Pb (II), among other ions. The BC was investigated by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared IV-TF and linear scanning voltammetric techniques and subsequently used in the construction of the electrodes. This work deals with the development and application of an EPCMBC modified barley bagasse (Hordeum vulgare) carbon paste electrode for the voltammetric determination of Pb (II) by a simple, fast and sensitive procedure. EPCMBC showed repeatability and reproducibility and linear response between 1 x 10-2 mol L-1 and 5 x 10-6 mol L-1 and detection limit of 3.7 x 10 - 6 mol L-1. The electrodes were also effectively used to determine Pb (II) in lipstick samples. Interference ions were studied in lead (II) analyzes with Ba2 +, Cr3 +, Cu2 +, Fe3 +, Zn2 + ions and the electrode was also effective. Thus, EPCMBC shows great potential to be applied in the voltammetric determination of Pb (II) in real samples.
Electrodes modified with barley bagasse (hordeum vulgare) developed for the voltammetric determination of Pb (II) on lipstick samples
Keywords: Eletrodos modificados; Voltametria de redissolução; Adsorção de metais; Bagaço de cevada (Hordeum vulgare); modified electrodes; Redissolution voltammetry; Metal adsorption; Barley bagasse (Hordeum vulgare); CIENCIAS EXATAS E DA TERRA::QUIMICA